Changes in microRNA expression in response to Schistosoma japonicum infection. (February 2017) - Hong, Y.; Fu, Z.; Cao, X.; Lin, J.
Summary: Schistosomiasis japonicum is one of the most serious zoonotic diseases in the world. There is increasing evidence to show that host miRNAs are modulated following Schistosoma japonicum infection, and some of these miRNAs may play important regulatory roles in response to schistosome infection. Several host miRNAs have been identified and shown to be potential diagnostic biomarkers or novel therapeutic targets for schistosomiasis. These studies have paved the way to a better understanding of the mechanisms of schistosome‐host interaction and may facilitate the development of novel approaches to the control of the disease.